Sosialisasi Bahan Baku Pembuatan Kapal Dan Perlindungan Lingkungan Maritim Bagi Masyarakat Nelayan Juwana - Indah Saraswati; Karolus Geleuk Sengadji; Dian Kurnianing Sari; Pranyoto Pranyoto (Jurnal Insan Pengabdian Indonesia, 2023)
The purpose of this community service activity is to provide socialization to the Juwana fishing community regarding the management of raw materials for making fishing boats in protecting the maritime environment and provide solutions to find alternative raw materials so that the vessels are in proper condition and safe to operate. This activity was held at the UPP class 3 Juwana meeting building, Pati Regency on March 20-22 2023. This community service activity was carried out through several stages including the preparation stage, field survey, activity planning, implementation in the form of counseling and evaluation. The implementation of this community service was enthusiastically welcomed by the Juana fishing community because this activity can add insight into the raw materials for shipbuilding so that people can be more careful and protect the environment